Profile and potential role of novel metabolite biomarkers, especially indoleacrylic acid, in pathogenesis of neuromyelitis optica spectrum disorders - Bian, Jiangping; Sun, Jiali; Chang, Haoxiao; Wei, Yuzhen; Cong, Hengri; Yao, Mengyuan; Xiao, Fuyao; Wang, Huabing; Zhao, Yaobo; Liu, Jianghong; Zhang, Xinghu; Yin, Linlin (Frontiers in Pharmacology, 2023)
Background: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune central nervous system (CNS) inflammatory and demyelinating disorder that can lead to serious disability and mortality. Humoral fluid biomarkers with specific, convenient, and efficient profiles that could characterize and monitor disease activity or severity are very useful. We aimed to develop a sensitive and high throughput liquid chromatography-tandem mass spectrometry (LC-MS)/MS-based analytical method for novel biomarkers finding in NMOSD patients and verified its function tentatively. Methods: Serum samples were collected from 47 NMOSD patients, 18 patients with other neurological disorders (OND) and 35 healthy controls (HC). Cerebrospinal fluid (CSF) samples were collected from 18 NMOSD and 17 OND patients. Three aromatic amino acids (phenylalanine, tyrosine, and tryptophan) and 9 important metabolites including phenylacetyl glutamine (PAGLN), indoleacrylic acid (IA), 3-indole acetic acid (IAA), 5-hydroxyindole acetic acid (HIAA), hippuric acid (HA), I-3-carboxylic acid (I-3-CA), kynurenine (KYN), kynurenic acid (KYNA), and quinine (QUIN) were analyzed by LC-MS/MS-based method. The profile of IA was further analyzed and its function was verified in an astrocyte injury model stimulated by NMO-IgG which represents important events in NMOSD pathogenesis. Results: In serum, tyrosine and some of the tryptophan metabolites IA and I-3-CA decreased and HIAA increased significantly in NMOSD patients. CSF levels of phenylalanine and tyrosine showed a significant increase exactly during the relapse stage and IA in CSF was also increased markedly during the relapse and remission phases. All conversion ratios have similar profiles with their level fluctuations. In addition, serum IA levels negatively correlated with glial fibrillary acidic protein (GFAP) and neurofilament light (NfL) in the serum of NMOSD patients measured by ultra-sensitive single-molecule arrays (Simoa). IA showed an anti-inflammatory effect in an in vitro astrocyte injury model. Conclusion: Our data suggest that essential aromatic amino acid tryptophan metabolites IA in serum or CSF may serve as a novel promising biomarker to monitor and predict the activity and severity of NMOSD disease. Supplying or enhancing IA function could promote anti-inflammatory responses and have therapeutic benefits.